Prediction of flammability limits for ethanol-air blends by the Kriging regression model and response surfaces - Gutiérrez Velásquez, Elkin I.; Coronado, Christian J.R.; Quintero Cartagena, Juan C.; Carvalho, João A. [UNESP]; Mendiburu, Andrés Z. [UNESP]; Andrade, José C.; Cortez, Ely V.; Santos, José C. (Elsevier, 2017)
Flammability limits must be identified in order to assess and control handling risks of particular processes according to combustion product composition and environmental conditions. Thereby, the present paper aims to present a model that can predict flammability limits for ethanol-air blends with at different moisture concentrations by Kriging interpolation techniques. The model is based on experimental results to determine flammability limits of ethanol-air blends, and evaluate different moisture concentrations in ethanol composition. It has accurately predicted the flammability limits of ethanol-air blends at temperatures ranging between 20 °C and 210 °C, pressure values ranging from 40 kPa to 101.3 kPa, ethanol moisture concentration at 0.5% and 8%, and ethanol volume percentages from 1% to 35%. Thus, it is a valid tool to accurately and efficiently determine flammability limits of ethanol-air blends.
Keywords: Ethanol; Experimental data; Flammability limits; Kriging; Response Surface Methodology